The effectiveness of using fennel meal (Foeniculum vulgare) in feeding young quails - T. Kholiavska; D. Umanets; O. Tytariova; R. Umanets (Тваринництво та технології харчових продуктів, 2025)
Fennel seeds are considered a potent phytobiotic and can be used in the feeding of young poultry as an alternative to antibiotics, which are applied to improve poultry performance and prevent a range of gastrointestinal diseases. The conducted scientific and economic study focused on examining the impact of feeding fennel seed cake on the performance and slaughter qualities of meat-type quails. According to the results of the experiment, among the investigated doses of fennel seed cake, specifically 0.5%, 1.0%, and 1.5%, the highest productivity was achieved by birds consuming full-feed compound feed containing 1.5% of the mentioned feed additive. The quails in this group exceeded the control group by 9.75 g or 3.44% in weight. With 1.0% fennel seed cake in the compound feed, the body weight of the birds was 7.07 g or 2.50% higher than the control group. When consuming compound feed containing 0.5% fennel seed cake, the quails surpassed the control group by only 4.55 g or 1.61%. It should be noted that the difference between the groups in terms of body weight was not statistically significant. The yield of carcasses slightly differed from the control, with quails consuming 1.5% fennel seed cake in the feed having a 0.1% higher yield. Regarding the yield of edible parts of the carcass, the trend towards an increased yield of breast muscles in the birds of the experimental groups was noteworthy, as well as the increased yield of the stomach, which was confirmed by the statistical significance of the difference between the control group and the birds consuming 1.5% fennel seed cake. Thus, it can be stated that feeding up to 1.5% fennel seed cake in full-feed compound feed has a positive effect on the productivity of meat-type quails